Effect of silica fume and fly ash on the stability of bound chlorides in cement mortar during electrochemical chloride extraction. (30th September 2020) - Zhu, Zhengyu; Chu, Hongqiang; Guo, Ming-zhi; Shen, Mingxia; Jiang, Linhua; Yu, Libo
Highlights: ·The effects of silica fume and fly ash on the stability of bound chloride ions were studied. ·The mechanisms of chloride instability were analyzed. ·The distribution of free chloride ions after electrochemical cloride extraction was investigated. Abstract: This study investigated the stability of bound chloride ions in the cement mortars incorporating supplementary cementitious materials (SCM) during the electrochemical chloride extraction (ECE) process. The effect of the replacing ratio of fly ash (FA) and silica fume (SF) and sulfate concentration on the chloride binding and distribution after ECE treatment was studied using water and acid-soluble methods, X-ray diffraction (XRD) analysis and thermogravimetric analysis (TGA). The results showed that the concentration of the bound chlorides in the SCM incorporated cement mortars depended heavily on the content of Al2 O3 and the pH of the pore solution. Without ECE treatment, an increase in the FA content increased the concentration of bound chlorides while the addition of SF significantly decreased the chloride binding capacity. During ECE treatment, however, the stability of bound chlorides declined with increasing the FA content but increased with increasing the SF content under an electric field. It was also found that the presence of sulfate ions reduced the content of the chemically bound chlorides residing in Friedel's salts (FS) but had a negligible influence on the physically bound chlorides absorbed by calcium silicate hydrate (C-S-H gel).